2019
DOI: 10.1016/j.chemosphere.2019.01.015
|View full text |Cite
|
Sign up to set email alerts
|

A new methodology to assess the performance of AOPs in complex samples: Application to the degradation of phenolic compounds by O3 and O3/UV-A–Vis

Abstract: A methodology combining experimental design methodology, liquid chromatography, excitation emission matrixes (EEM) and bioassays has been applied to study the performance of O3 and O3/UVA-vis in the treatment of a mixture of eight phenolic pollutants. An experimental design methodology based on Doehlert matrixes was employed to determine the effect of pH (between 3 and 12), ozone dosage (02-1.0 g/h) and initial concentration of the pollutants (1-6 mg/L each). The following conclusions were obtained: a) acidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…According to the commonly used oxidants in water treatment [33], besides the PS and H 2 O 2 , ozone (O 3 ) may be a compromised alternative for N-compounds digestion, and which can generate •OH by self-decomposition in basic medium or under certain conditions such as UV, ultrasound (US) and microwave (MW) [34,35]. Although ozone has been widely used in water treatment as disinfectant and oxidant, in which transformation of organic micropollutants occurs via direct reaction with O 3 or indirect reaction with hydroxyl radicals [36][37][38][39][40], fewer studies have reported its use for digestion and determination of TDN in waters. Considering the oxidation capacity, safety, self-degradability, removal ability and convenience of oxidant, O 3 was selected as the oxidant for digestion of N-compounds, and then will use UV and/or US to intensify its digestion ability in this study.…”
Section: Introductionmentioning
confidence: 99%
“…According to the commonly used oxidants in water treatment [33], besides the PS and H 2 O 2 , ozone (O 3 ) may be a compromised alternative for N-compounds digestion, and which can generate •OH by self-decomposition in basic medium or under certain conditions such as UV, ultrasound (US) and microwave (MW) [34,35]. Although ozone has been widely used in water treatment as disinfectant and oxidant, in which transformation of organic micropollutants occurs via direct reaction with O 3 or indirect reaction with hydroxyl radicals [36][37][38][39][40], fewer studies have reported its use for digestion and determination of TDN in waters. Considering the oxidation capacity, safety, self-degradability, removal ability and convenience of oxidant, O 3 was selected as the oxidant for digestion of N-compounds, and then will use UV and/or US to intensify its digestion ability in this study.…”
Section: Introductionmentioning
confidence: 99%
“…EEM-PARAFAC is still in constant improvement, with its application with real-time continuous monitoring [133], machine learning [134], or even for laboratory-scale fluorescence of CECs simultaneous degradation analysis employing AOPs: from heavy polycyclic aromatic hydrocarbons [135], polyphenols [136] to FQs antibiotics [119,137], the latter shown in the Results and Discussion chapter. Therefore, besides from the simultaneous monitoring of the several parent pollutants that can be obtained in a simple, economical and fast way, it can also be elucidated the plausible molecular changes when observing new deconvoluted components corresponding to oxidation by-products.…”
Section: Examples Of the Eem-parafac Use Within The Water Treatment Studiesmentioning
confidence: 99%
“…2.1, where Lac is the accumulated irradiation (W min), Vi the irradiated volume (m 3 ), Si the irradiated surface (m 2 ) and VT the total volume (m 3 ). The accumulated light is therefore normalized by the solar average intensity, L, which is reported to be 30 W m -2 in Southern Spain [140,141].…”
Section: Irradiationsmentioning
confidence: 99%
See 2 more Smart Citations